2007
DOI: 10.1007/s00432-007-0325-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cFLIP in head and neck squamous cell carcinoma and its clinicopathologic correlations

Abstract: Overexpression of cFLIP(L) is a frequent event in HNSCC and HNSCC cells in vivo may need it to evade apoptosis mediated by Fas or other receptors, which might contribute to tumour development and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Furthermore, the overexpression of cFLIP attenuated apoptosis induced by FPDHP. cFLIP has been identified as an inhibitor of apoptosis triggered by the engagement of death receptors, such as Fas or TRAIL, and abnormal cFLIP expression has been identified in various types of cancer (21,22). Therefore, this suggests that the transcriptional downregulation of cFLIP by FPDHP may be important for the induction of FPDHP-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the overexpression of cFLIP attenuated apoptosis induced by FPDHP. cFLIP has been identified as an inhibitor of apoptosis triggered by the engagement of death receptors, such as Fas or TRAIL, and abnormal cFLIP expression has been identified in various types of cancer (21,22). Therefore, this suggests that the transcriptional downregulation of cFLIP by FPDHP may be important for the induction of FPDHP-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 96%
“…The results showed that these genes were downregulated when IKKa and IKKb were knocked down in both in vivo and in vitro assays. The c-FLIP and Bcl-xl were highly expressed in human malignancy, [28][29][30][31][32] and we found that the transcription level of c-FLIP was significantly increased in human HCC tissue, whereas there was no difference in Bcl-xl transcription level. Nevertheless, Bcl-xl is a significant prognostic factor for disease progression in human HCC, because the actual effect of this gene is not determined by its expression level but rather by the rate of deamidation.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression levels of c-FLIP have been reported in colorectal cancer [67,68], bladder urothelial cancer [69], cervical cancer [70], Burkitt's lymphoma [71], non-Hodgkin's lymphoma [72], Head and Neck Squamous Cell Carcinoma (HNSCC) [73], hepatocellular cancers [74], and high-grade prostatic intraepithelial neoplasia (HGPIN) with maximal c-FLIP expression detected in Castrate-Resistant Prostate Cancer (CRPC) [75]. c-FLIP upregulation is also seen in gastric cancer and plays an important role in lymph node metastasis, which ultimately contributes to tumor progression [76].…”
Section: Upregulation Of C-flip In Human Cancersmentioning
confidence: 99%